2016
DOI: 10.1016/j.epsl.2016.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Full-field predictions of ice dynamic recrystallisation under simple shear conditions

Abstract: Understanding the flow of ice on the microstructural scale is essential for improving our knowledge of large-scale ice dynamics, and thus our ability to predict future changes of ice sheets. Polar ice behaves anisotropically during flow, which can lead to strain localisation. In order to study how dynamic recrystallisation affects to strain localisation in deep levels of polar ice sheets, we present a series of numerical simulations of ice polycrystals deformed under simple-shear conditions. The models explici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 48 publications
4
67
0
Order By: Relevance
“…Recent microstructural modelling studies [18,19,112] combined deformation by a viscoplastic full-field approach (taking strong crystal anisotropy into account [113]) with recrystallization (dynamic and static, continuous and discontinuous [114]). These simulations suggested that the effect of recrystallization on the LPO should be minor.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent microstructural modelling studies [18,19,112] combined deformation by a viscoplastic full-field approach (taking strong crystal anisotropy into account [113]) with recrystallization (dynamic and static, continuous and discontinuous [114]). These simulations suggested that the effect of recrystallization on the LPO should be minor.…”
Section: Resultsmentioning
confidence: 99%
“…Under these conditions, grain boundary migration dominates the microstructure evolution and masks the deformation habitus of grains [18,19]. This has been observed with respect to the appearance of triple junctions [17] as well as grain boundary irregularities [77].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations